2022
DOI: 10.1021/acs.jpcc.1c10866
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Exfoliation of Transition-Metal Dichalcogenides by Amino Acid in Water for Promoting Hydrogen Evolution Reaction

Abstract: Two-dimensional transition-metal dichalcogenides (TMDs) are promising as efficient and earth-abundant electrocatalysts for the hydrogen evolution reaction (HER). However, only the edge and defect sites show HER catalytic properties, while the basal plane, which has nonexistent unsaturated sites, is inactive. Herein, we tackle the key challenge of increasing the number of electrocatalytic sites by using a general and facile method for the effective layer-by-layer exfoliation of TMDs in water by using an amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…[ 232–234 ] Theoretical calculations indicated that the Gibbs free energy of the edge sites of MoSe 2 was lower than that of the edge sites of MoS 2 , leading to the superior HER performance of MoSe 2 . [ 235–237 ] However, the active catalytic sites are located only at the narrow edge sides, whereas the basal plane of MoSe 2 is inert. In addition, its inferior conductivity hinders electron transfer, resulting in unfavorable resistance.…”
Section: Energy Applications Of Mose2mentioning
confidence: 99%
“…[ 232–234 ] Theoretical calculations indicated that the Gibbs free energy of the edge sites of MoSe 2 was lower than that of the edge sites of MoS 2 , leading to the superior HER performance of MoSe 2 . [ 235–237 ] However, the active catalytic sites are located only at the narrow edge sides, whereas the basal plane of MoSe 2 is inert. In addition, its inferior conductivity hinders electron transfer, resulting in unfavorable resistance.…”
Section: Energy Applications Of Mose2mentioning
confidence: 99%